Targeting PIM Kinases to Improve the Efficacy of Immunotherapy - Amber N. Clements; Noel A. Warfel (Cells, 2022)
The Proviral Integration site for Moloney murine leukemia virus (PIM) kinases is a family of serine/threonine kinases that regulates numerous signaling networks that promote cell growth, proliferation, and survival. PIM kinases are commonly upregulated in both solid tumors and hematological malignancies. Recent studies have demonstrated that PIM facilitates immune evasion in cancer by promoting an immunosuppressive tumor microenvironment that suppresses the innate anti-tumor response. The role of PIM in immune evasion has sparked interest in examining the effect of PIM inhibition in combination with immunotherapy. This review focuses on the role of PIM kinases in regulating immune cell populations, how PIM modulates the immune tumor microenvironment to promote immune evasion, and how PIM inhibitors may be used to enhance the efficacy of immunotherapy.